Response of Long-term Cyclic Laterally Loaded Monopiles in Sand - Khalaf, M. M.; El-Sherbeiny, Rami M.; Ebid, Ahmed M.; Agaiby, Shehab S. (Civil Engineering Journal, 2025)
The offshore wind energy industry has grown rapidly, with large-diameter monopiles becoming the primary foundation choice for offshore turbines. Monopile designs emphasize serviceability and fatigue limits, enforcing strict rotation limits set by manufacturers. These structures face considerable lateral cyclic loads from waves, currents, and wind. Existing design codes such as API and DNV GL are commonly used but do not sufficiently capture monopile behavior under cyclic loading, particularly regarding load cycle count, amplitude, and type. Moreover, the dynamic response of the monopile-soil system, which affects the foundation’s natural frequency, depends on the pile-soil interaction stiffness—an aspect neglected in current standards. This research reports results from seventeen 1-g cyclic loading experiments and six monotonic tests on monopiles installed in dry sand. Findings reveal that cyclic deformation is significantly influenced by sand relative density, load cycle number, and cyclic load characteristics (magnitude and type). Cyclic loading also alters the pile-soil stiffness. Accumulated rotation grows exponentially with increasing load cycles, while cyclic secant stiffness increases logarithmically. The study further identifies asymmetric two-way cyclic loading as the most damaging load pattern for monopile performance.